A Study on The effectiveness of time management among secondary school principals in Damascus Governorate - ZEINUDDINE, ZAHER NUHAIL (2018)
This study aims to identify the average time spent by the secondary school principals in Damascus Governorate from the official working time on all tasks required by virtue of their position for each level of school management: administrative, technical and social. Moreover, to detect the impact of independent variables of the principal, school, and educational zone. The study sample consisted randomly of (70) principals, representing 75% of the total study society. A tool developed based on educational literature and questionnaires used in previous studies. Then presented it to arbitrators at the British University in Dubai and the University of Damascus, to verify its authenticity. Stability verified using (Cronbach Alpha). The questionnaire consisted of three parts: the principal’s data, school, and educational zone, the amount of time spent on the day-to-day administrative work, and time management according to the three administrative levels. The study results are: 1. A difference in total working hours between male and female managers. 2. A difference in the performance time of various administrative tasks. 3. A difference in ordering tasks according to their importance. 4. No differences in time management performance according to the independent variables. Based on the results, the researcher set important recommendations, such as to adopt the results and recommendations of this study, and to organize training courses for managers to improve their time management skills.